A Drop-in Gamma Probe for Minimally Invasive Sentinel Lymph Node Dissection in Prostate Cancer: Preclinical Evaluation and Interim Results From a Multicenter Clinical Trial. (14th March 2023) - Abascal Junquera, Jose M.; Harke, Nina N.; Walz, Jochen C.; Hadaschik, Boris; Adshead, Jim; Everaerts, Wouter; Goffin, Karolien; Grootendorst, Maarten R.; Oldfield, Francesca; Vyas, Kunal; Fusco, Antoni Mestre; Juanpere, Nuria; et al.
Abstract : Purpose: This study evaluated the performance of a drop-in gamma probe for prostate cancer (PCa) sentinel lymph node dissection (SLND) in a pelvic phantom, porcine model, and in PCa patients as part of an ongoing prospective multicenter clinical trial. Methods: Two design variants of the drop-in gamma probe (SENSEI; Lightpoint Medical Ltd) were assessed in the pelvic phantom, and the preferred design was evaluated in a porcine model with clinically representative volumes and 99m Tc activities. In the clinical trial, radical prostatectomy, SLND, and extended pelvic lymph node dissection were performed the day after 99m Tc-nanocolloid injection and imaging. Sentinel lymph nodes (SLNs) were detected with the drop-in probe and a rigid laparoscopic gamma probe (RLGP). An interim analysis was performed after 10 patients were recruited. Results: The narrow field of view probe design outperformed the wide field of view design in the pelvic phantom (detection rate, 100% vs 50%). In the porcine model, all activity concentrations could be successfully detected. The drop-in gamma probe successfully detected SLNs in all 10 patients (detection rate, 100%). Two of the SLNs identified by the drop-in gamma probe could not be found with the RLGP. No false-negative cases and no adverse events related to the SLND procedure or the drop-in gamma probe occurred. Conclusion: The drop-in gamma probe meets the usability and performance requirements for SLND in PCa and provides performance advantages over the RLGP. The final clinical study results will confirm the performance of the technique across multiple sites.